TEM Studies of ZnS Nanoparticles Obtained by Wet Chemical Reaction - Di Stefano, M. C.; Cabanillas, Edgardo Domingo; Trigubo, Alicia Beatriz; RodrÍguez Torres, Claudia Elena; Walsöe de Reca, N. E. (Comité Interamericano de Sociedades de Microscopía Electrónica, 2010)
Fil: Di Stefano, M. C.. Universidad Tecnológica Nacional. Facultad Regional Buenos Aires; Argentina